ANALYSIS OF TEACHING MATERIALS FOR AKIDAH AKHLAK WITH THE APPROACH OF BENJAMIN S. BLOOM THEORY - Muna, Lia Rif’atul; Miftah, Muhammad; Nurtaqim, Ahmad Basori; Bahauddin, Muhammad Irfan (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
The purpose of this study is to analyze the teaching material of Akidah Akhlak class VII semester I chapter II published by the Directorate of KSKK Madrasah, Directorate General of Islamic Education and Ministry of Religious Affairs of the Republic of Indonesia, in particular analysing the material in Chapter II and its relevance to the theory of Benjamin S Bloom which covers three domains namely cognitive, affective, and psychomotor domain as well as from the psychological point of view of student development. This research uses a qualitative approach using a library study or library research research method by searching literature involving books, journals, and other sources of information relevant to the subject being studied. The results of this examination are the content of the learning material Akidah Akhlak is already in line with the cognitive theory, and affective Benjamin S Bloom but in the psychomotor aspects of this chapter is not very emphasized because of the material about the properties of God where students only need to know, understand apply, and believe the qualities of God along with the signs that have been mentioned in it, while psychologically the development of the students of this book from the language aspects is quite easy to understand for children age MTs (13-15 years) where the brain development and cognition of the child has developed. However, in the presentation of the data table, God's properties are less attractive to readers and the images displayed are less clear. In spite of all that teaching material especially in chapter II about the attributes of God is already sufficient. Having quality teaching materials can help teachers to deliver learning materials well, with the right methods of teachers and involve students actively in learning in order to the learning goals set by the government and advance education in Indonesia.   Keywords:. Akidah Akhlak; Teaching Materials; Benjamin S Bloom.